Case of aggressive metastatic follicular variant papillary thyroid carcinoma with BRAF K601E and BCORL1 mutations. Issue 6 (30th June 2020) - Attia, Doaa; Lurie, Alexander; Zhai, Qihui; Mesko, Thomas; Smallridge, Robert
Abstract : BCL6 corepressor like-1 (BCORL1) mutation has rarely been described in thyroid cancer or in association with BRAF mutations in any malignancy. However, we report a 49-year-old woman who had aggressive follicular variant papillary thyroid carcinoma (FV-PTC) with both the BRAF K601E and BCORL1 mutations. The patient underwent a total thyroidectomy for a 3.6 cm right thyroid nodule and a smaller lesion in the left lobe in 2007; both were FV-PTCs with no lymphovascular invasion or metastases. In 2015, a positron emission tomography–CT scan showed a small defect in the left posterior lateral fifth rib with mild increased hypermetabolic activity with standardised uptake value of 3.9 and another lesion in the right hip at the junction of the femoral neck and trochanter. Tumour biopsy and genetic analysis revealed an uncommon BRAF K601E and a rare BCORL1 mutation. While rare, we report a case of aggressive FV-PTC with both the BRAF K601E and BCORL1 mutations.